The Quality and Public Trust Based Marketing Management of Islamic Boarding School Educational Services - Irzhal Fauzi, Irzhal Fauzi (Journal Of Islamic Education And Pesantren, 2023)
Competition among educational institutions in the era of globalization requires Islamic boarding schools (pesantren) to manage and market their educational services professionally while maintaining Islamic values and the distinctive character of pesantren education. This study aims to analyze the management of educational service marketing based on quality improvement and public trust at Pondok Pesantren Miftahul Mubtadiin Krempyang Tanjunganom Nganjuk, as well as to identify the challenges and strategies employed to address them. This research adopted a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation, and analyzed using descriptive qualitative techniques. The findings indicate that Pondok Pesantren Miftahul Mubtadiin implements educational service marketing management based on the marketing mix (7P), including the provision of integrated educational programs from early childhood education to higher education, affordable tuition fees, a strategic location, promotional strategies relying on alumni networks and students’ moral exemplarity as a foundation of public trust, open and responsive educational services, competent teaching staff, and adequate facilities and infrastructure. However, the implementation of these strategies faces several challenges, such as alumni behavior that does not fully reflect pesantren values, limited support from students’ guardians, and a shortage of administrative personnel. To address these challenges, the pesantren has undertaken efforts to enhance educational quality and students’ moral development, strengthen program socialization to parents, and involve third-year Madrasatul ‘Ulya students in supporting pesantren administrative tasks.